A high-capacity oligographene and low-temperature preparation method thereof
By adopting specific preparation methods under low temperature conditions, including mixing of graphite powder and sodium nitrate and the addition of oxidants, subsequent water bath reactions and multiple dilution, filtering, and washing are finally frozen and dry in high vacuum environments. High -capacity oligochrite graphene compared with the surface area and high -level guidance rate solves the problem of low -temperature preparation in the existing technology, and achieves high -efficiency and low -cost technologies.
Patent Information
- Application Number
- CN202411510141.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The prior art is difficult to prepare high-capacity oligosheet graphene with high specific surface area under low temperature conditions, and the preparation process is complex and the cost is high.
Using a low -temperature preparation method, mixing graphite powder and sodium nitrate with mixed acids, stir under ice water bath conditions, and slowly add oxidatives, and then respond to water bath in constant temperature water. Frozen and dry in the vacuum environment to prepare high -capacity oligoplasty graphene.
Under low temperature conditions, oligne graphene has a high ratio (200-800m2/g), electrochemical ratio (140-180F/G) and high-conductivity (> 104S/m). Low, and the nature of the materials produced is more stable.
Smart Images

Figure CN119018884B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of oligographene preparation, and in particular, relates to high-capacity oligographene and a low-temperature preparation method thereof. Background Art
[0002] Graphene is a single layer of carbon atoms in sp 2 The two-dimensional carbon nanomaterial with hexagonal honeycomb lattice composed of hybrid orbitals has an extremely high specific surface area. When the graphene sheets are stacked by single layer, double layer or several layers, it is a high-capacity oligo-sheet graphene. This kind of high-capacity oligo-sheet graphene has the characteristics of high conductivity, high strength and toughness, ultra-large specific surface area, excellent thermal conductivity, good chemical stability, high light transmittance, etc. It has a wide range of application scenarios in the electronics industry, new energy field, materials science field, biomedicine field and other fields. The high specific surface area of high-capacity oligo-sheet graphene means that it can provide more active sites, thereby increasing the contact area with the electrolyte and improving the capacity and performance of energy storage devices.
[0003] The so-called specific surface area refers to the surface area per unit mass of graphene. Since graphene is a two-dimensional material composed of a single layer of carbon atoms and its thickness is only one atomic layer, it can have a huge surface area even if its mass is very small. However, the specific surface area of the actually prepared graphene may deviate from the theoretical value due to defects, impurities, number of layers and other factors. Therefore, the specific surface area of graphene needs to be accurately measured and evaluated according to the specific situation. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a high-capacity oligographene sheet and a low-temperature preparation method thereof. The oligographene sheet prepared under low-temperature conditions has the excellent performance of high specific surface area.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A low-temperature preparation method for preparing the above-mentioned high-capacity oligographene is carried out according to the following steps:
[0007] S1: Evenly mix 5±0.5g of graphite powder and 1±0.5g of sodium nitrate with 150±10mL of mixed acid, stir in an ice-water bath, slowly add an oxidant during stirring, and react for 2-3 hours to obtain a mixed solution;
[0008] S2: Transfer the mixed solution to a constant temperature water bath at 35±5°C for a reaction time of 30±5 min; gradually add 92±5 mL of deionized water to the mixed solution, and then heat the mixed solution to 98±2°C for a further reaction of 3±0.5 h, and then remove the mixed solution from the water bath;
[0009] S3: Continue to add 30 mL of deionized water to the mixed solution treated in step S2 and dilute it with 30 ± 2 mL of H 2 O 2 The unreacted oxidant in the solution is neutralized and the mixed solution is centrifuged to obtain a precipitate in the solution;
[0010] S4: washing the precipitate obtained in step S3 twice with hydrochloric acid under suction filtration conditions, and then washing the precipitate with distilled water until the pH value is 5-7;
[0011] S5: placing the washed precipitate in a centrifuge for centrifugal treatment to separate the precipitate to obtain oligographene production raw materials;
[0012] S6: Then, the oligographene production raw material is placed in a vacuum environment of 0.01Pa-10kPa, and then heated to -60--80°C at a heating rate of 1-5°C / min for high vacuum freezing treatment, and maintained at a constant temperature for 48-72h for freeze drying to obtain the oligographene material.
[0013] The following is a further optimization of the above technical solution by the present invention:
[0014] In step S1, the mass concentration of the mixed acid is 98%.
[0015] Further optimization: In step S1, the mixed acid is a mixed solution of concentrated sulfuric acid, nitric acid and phosphoric acid, and the amount of concentrated sulfuric acid is 120 mL, the amount of nitric acid is 10-20 mL, and the amount of phosphoric acid is 10-20 mL by volume.
[0016] Further optimization: In step S1, the oxidant is KMnO 4 , the KMnO 4 The dosage is 5±0.5g.
[0017] Further optimization: In step S3, H 2 O 2 The mass concentration of the solution is 30%.
[0018] Further optimization: In step S3, the mass concentration of H 2 O 2 The solution preparation process is as follows: measure H 2 O 2 3 mL of solution was added and diluted with 27 mL of water to obtain a 30% H 2 O 2 Solution.
[0019] Further optimization: In step S4, the concentration of hydrochloric acid is 0.1 mol / L.
[0020] Further optimization: In step S5, the centrifugal speed of the centrifuge is 8000±500r / min, and the centrifugal treatment time is 5-10min.
[0021] The present invention also provides a high-capacity oligographene prepared by the low-temperature preparation method, which has the following physical parameters: the oligographene sheet thickness is 0.35-20nm, the specific surface area is 200-800m 2 / g, electrochemical specific capacity is 140-180F / g; conductivity>10 4 S / m.
[0022] The present invention adopts the above technical scheme, has an ingenious conception, prepares oligographene under low temperature conditions, has a simple process, has low operating cost, reduces the requirements for production equipment, and the entire reaction process is stable and controllable. The oligographene produced has more stable properties. The specific surface area of the oligographene prepared by this method is 200-800m 2 / g, this property makes oligographene have great application potential in surface chemistry, adsorption, energy storage materials, gas sensors, environmental protection and seawater desalination, and is a material with market prospects and wide applications.
[0023] The present invention is further described below in conjunction with the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM image of 8-10 layers of oligographene in an embodiment of the present invention when the scale is 10 μm;
[0025] Figure 2 This is a SEM image of 8-10 layers of oligographene in an embodiment of the present invention when the scale is 1 μm. DETAILED DESCRIPTION
[0026] Example 1: Figure 1-2 As shown, a low-temperature preparation method of high-capacity oligographene comprises the following steps:
[0027] S1: 4.5 g of graphite powder and 0.5 g of sodium nitrate were uniformly mixed with 140 mL of a mixed acid having a mass concentration of 98%, and stirred in an ice-water bath. During the stirring process, an oxidant was slowly added, and the mixture was reacted for 2 hours to obtain a mixed solution.
[0028] In the step S1, the mixed acid is a mixed solution of concentrated sulfuric acid, nitric acid and phosphoric acid, and the amount of the concentrated sulfuric acid is 120 mL, the amount of nitric acid is 10 mL, and the amount of phosphoric acid is 10 mL by volume.
[0029] In step S1, the oxidant is KMnO 4 , the KMnO4 The dosage is 4.5g.
[0030] S2: The mixed solution was transferred to a constant temperature water bath at 30°C for a reaction time of 25 min; 87 mL of deionized water was gradually added to the mixed solution, and then the mixed solution was heated to 96°C for a further reaction of 2.5 h, and then the mixed solution was taken out of the water bath;
[0031] S3: Continue to add 30 mL of deionized water to the mixed solution treated in step S2 and dilute it with 28 mL of 30% H 2 O 2 The unreacted KMnO in the solution and the mixed solution 4 , centrifugally filter the mixed solution to obtain a precipitate in the solution;
[0032] In step S3, the mass concentration of H 2 O 2 The solution preparation process is as follows: measure H 2 O 2 3 mL of solution was added and diluted with 27 mL of water to obtain a 30% H 2 O 2 Solution.
[0033] S4: washing the precipitate obtained in step S3 twice with 0.1 mol / L hydrochloric acid under suction filtration, and then washing the precipitate with distilled water until the pH value is 5;
[0034] S5: placing the washed precipitate in a centrifuge and centrifuging it at a speed of 7500 r / min for 5 minutes; separating the precipitate to obtain a raw material for producing oligographene.
[0035] S6: placing the oligographene production raw material processed in step S5 in an environment with a vacuum degree of 0.01 Pa, and then heating it to -60°C at a heating rate of 1°C / min for high vacuum freezing treatment, maintaining a constant temperature for 48 hours for freeze drying, and after the treatment is completed, obtaining the oligographene material.
[0036] Embodiment 2: A low-temperature preparation method of high-capacity oligographene comprises the following steps:
[0037] S1: Evenly mix 5g of graphite powder and 1g of sodium nitrate with 150mL of 98% mixed acid, stir in an ice-water bath, and slowly add 5g of KMnO 4 , react for 2.5 hours to obtain a mixed solution.
[0038] In the step S1, the mixed acid is a mixed solution of concentrated sulfuric acid, nitric acid and phosphoric acid. By volume, the amount of concentrated sulfuric acid is 120 mL, the amount of nitric acid is 15 mL, and the amount of phosphoric acid is 15 mL.
[0039] S2: The mixed solution was transferred to a water bath at a constant temperature of 35°C for a reaction time of 30 min; 92 mL of deionized water was gradually added to the mixed solution, and then the mixed solution was heated to 98°C for a further reaction of 3 h, and then the mixed solution was removed from the water bath;
[0040] S3: Continue to add 30 mL of deionized water to the mixed solution treated in step S2 to dilute it, and then add 30 mL of 30% H 2 O 2 The unreacted KMnO in the solution and the mixed solution 4 , centrifugally filter the mixed solution to obtain a precipitate in the solution;
[0041] S4: washing the precipitate obtained in step S3 twice with 0.1 mol / L hydrochloric acid under suction filtration, and then washing the precipitate with distilled water until the pH value is 6;
[0042] S5: placing the washed precipitate in a centrifuge, centrifuging at a speed of 8000 r / min for 8 min, separating the precipitate to obtain a raw material for oligographene production;
[0043] S6: placing the oligographene production raw material processed in step S5 in an environment with a vacuum degree of 5 kPa, and then heating it to -70°C at a heating rate of 3°C / min for high vacuum freezing treatment, maintaining a constant temperature for 60 hours for freeze drying, and after the treatment is completed, obtaining the oligographene material.
[0044] Embodiment 3: A method for preparing high-capacity oligographene at low temperature, comprising the following steps:
[0045] S1: 5.5 g of graphite powder and 1.5 g of sodium nitrate were uniformly mixed with 160 mL of a mixed acid with a mass concentration of 98%, and stirred in an ice-water bath. During the stirring process, 5.5 g of KMnO 4 , react for 3 hours to obtain a mixed solution.
[0046] In step S1, the mixed acid is a mixed solution of concentrated sulfuric acid, nitric acid and phosphoric acid. By volume, the amount of concentrated sulfuric acid is 120 mL, the amount of nitric acid is 20 mL, and the amount of phosphoric acid is 20 mL.
[0047] S2: The mixed solution was transferred to a constant temperature water bath at 40°C for a reaction time of 35 min; 97 mL of deionized water was gradually added to the mixed solution, and then the mixed solution was heated to 100°C and continued to react for 3.5 h, and then the mixed solution was taken out of the water bath.
[0048] S3: Continue to add 30 mL of deionized water to the mixed solution treated in step S2 and dilute it with 32 mL of 30% H 2 O 2 The unreacted KMnO in the solution and the mixed solution 4 , the mixed solution is centrifuged and filtered to obtain the precipitate in the solution.
[0049] S4: washing the precipitate obtained in step S3 twice with hydrochloric acid having a concentration of 0.1 mol / L under suction filtration conditions, and then washing the precipitate with distilled water until the pH value is 7.
[0050] S5: placing the washed precipitate in a centrifuge, and centrifuging it at a speed of 8500 r / min for 10 min to separate the precipitate to obtain a raw material for producing oligographene.
[0051] S6: placing the oligographene production raw material processed in step S5 in an environment with a vacuum degree of 10 kPa, and then heating it to -80°C at a heating rate of 5°C / min for high vacuum freezing treatment, maintaining a constant temperature for 72 hours for freeze drying, and after the treatment is completed, obtaining the oligographene material.
[0052] The physical properties of the oligographene sheets prepared in the above Examples 1-3 were tested, and the test items included: (1) specific surface area; (2) electrochemical specific capacity; (3) thickness of the oligographene sheets; and (4) electrical conductivity.
[0053] The inspection process of (1) specific surface area is carried out as follows:
[0054] B1. The oligographene prepared in Examples 1-3 are respectively placed into three corresponding sample tubes, and the three sample tubes are numbered to correspond to the oligographene in Examples 1-3. The three sample tubes are then evacuated to a vacuum degree of 10 Pa, and heating is started at the same time, with a heating rate of 5°C / min, and the temperature is raised to 200°C and maintained for 10 hours to obtain graphene oxide.
[0055] B2. The specific surface area of graphene oxide was measured by nitrogen adsorption. The adsorption temperature was liquid nitrogen temperature (77K). The specific surface areas of oligographene in Examples 1-3 were shown in the following table:
[0056] Serial number Specific surface area Example 1 210㎡ / g Example 2 300㎡ / g Example 3 780㎡ / g
[0057] As can be seen from the above table, the specific surface area of the oligographene prepared in Examples 1-3 is 200-800 m 2 / g.
[0058] (2) The electrochemical specific capacity test procedure is carried out as follows:
[0059] D1. First, 3 mg of the oligographene prepared in Examples 1-3 were weighed in sequence, and the electrochemical specific capacity of the oligographene prepared in Examples 1-3 was tested according to the following testing steps.
[0060] D2. The electrochemical specific capacity was tested using a three-electrode system with KOH as the electrolyte. The nickel foam was cut into square electrode sheets with a side length of 1*1 cm, and the sheets were dried at 120°C for 12 hours and then weighed.
[0061] D3. The oligographene obtained in step D1 was placed in a vacuum dryer at 100° C. for 5 h to degas, and then 0.3 mg of PVDF emulsion or PTFE emulsion and 0.3 mg of carbon black were dropped into the mixture. 2 mL of NMP was added, and ultrasonic dispersion was performed for 20 min to obtain a dispersion.
[0062] D4, then drip the above dispersion onto the nickel foam electrode sheet with a dropper, dry the electrode sheet with the dispersion dripped on it at 60°C for 12h, weigh it, calculate the effective mass of oligographene, and soak the prepared electrode sheet in KOH solution for 12h to measure its electrochemical performance; with Ag / AgCl as the reference electrode, the electrochemical specific capacity of oligographene in Examples 1-3 measured at a charge and discharge current of 100mA / g is shown in the following table:
[0063] Serial number Electrochemical specific capacity Example 1 142F / g Example 2 156F / g Example 3 178F / g
[0064] It can be seen from the above table that the electrochemical specific capacity of the oligographene prepared in Examples 1-3 is 140-180 F / g.
[0065] (3) Using a scanning electron microscope (SEM), the thickness of the oligographene sheets prepared in Examples 1-3 was measured.
[0066] The following table is a table showing the test results of the thickness of oligographene sheets in Examples 1-3:
[0067] Serial number Thickness of oligographene sheets Example 1 18nm Example 2 0.45nm Example 3 5.6nm
[0068] It can be seen from the above table that the thickness of the oligographene sheets prepared in Examples 1-3 is 0.35-20 nm.
[0069] (4) The conductivity of the oligographene sheets prepared in Examples 1-3 was detected using an electrochemical workstation; the conductivity of the oligographene sheets prepared in Example 1 was >105 S / m; the conductivity of oligographene prepared in Example 2 is >10 6 S / m; the conductivity of oligographene prepared in Example 3 is >10 4 S / m.
[0070] It can be seen that the conductivity of the oligographene prepared in Examples 1-3 is >10 4 S / m.
[0071] For those skilled in the art, according to the teachings of the present invention, without departing from the principles and spirit of the present invention, changes, modifications, substitutions and variations made to the implementation methods are still within the protection scope of the present invention.
Claims
1. A low-temperature preparation method for high-capacity oligographene, characterized in that: Proceed as follows: S1: Evenly mix 5±0.5g of graphite powder and 1±0.5g of sodium nitrate with 150±10mL of mixed acid, stir in an ice-water bath, slowly add an oxidant during stirring, and react for 2-3 hours to obtain a mixed solution; S2: Transfer the mixed solution to a constant temperature water bath at 35±5°C for a reaction time of 30±5 min; gradually add 92±5 mL of deionized water to the mixed solution, and then heat the mixed solution to 98±2°C for a further reaction of 3±0.5 h, and then remove the mixed solution from the water bath; S3: Continue to add 30 mL of deionized water to the mixed solution treated in step S2 to dilute it, and use 30±2 mL of H2O2 solution to neutralize the unreacted oxidant in the mixed solution, and centrifuge and filter the mixed solution to obtain a precipitate in the solution; S4: washing the precipitate obtained in step S3 twice with hydrochloric acid under suction filtration conditions, and then washing the precipitate with distilled water until the pH value is 5-7; S5: placing the washed precipitate in a centrifuge for centrifugal treatment to separate the precipitate to obtain oligographene production raw materials; S6: Then the oligographene production raw material is placed in an environment with a vacuum degree of 0.01Pa-10kPa, and then the temperature is raised to -60--80°C at a heating rate of 1-5°C / min for high vacuum freezing treatment, and the constant temperature is maintained for 48-72h for freeze drying to obtain the oligographene material; The oligographene obtained in steps S1-S6 has the following physical parameters: the thickness of the oligographene sheet is 0.35-20 nm, the specific surface area is 200-800 m 2 / g, electrochemical specific capacity is 140-180F / g; conductivity>10 4 S / m.
2. A low-temperature preparation method for high-capacity oligographene according to claim 1, characterized in that: In step S1, the mass concentration of the mixed acid is 98%.
3. A low-temperature preparation method for high-capacity oligographene according to claim 2, characterized in that: In step S1, the mixed acid is a mixed solution of concentrated sulfuric acid, nitric acid and phosphoric acid, and the amount of the concentrated sulfuric acid is 120 mL, the amount of nitric acid is 10-20 mL, and the amount of phosphoric acid is 10-20 mL by volume.
4. A low-temperature preparation method for high-capacity oligographene according to claim 3, characterized in that: In step S1, KMnO4 is used as the oxidant, and the amount of KMnO4 used is 5±0.5g.
5. A low-temperature preparation method for high-capacity oligographene according to claim 4, characterized in that: In step S3, the mass concentration of the H2O2 solution is 30%.
6. A low-temperature preparation method for high-capacity oligographene according to claim 5, characterized in that: In step S3, the preparation process of the H2O2 solution with a mass concentration of 30% is as follows: 3 mL of the H2O2 solution with a mass concentration of 100% is measured, and 27 mL of water is added to dilute it to obtain the H2O2 solution with a mass concentration of 30%.
7. A low-temperature preparation method for high-capacity oligographene according to claim 6, characterized in that: In step S4, the concentration of hydrochloric acid is 0.1 mol / L.
8. A low-temperature preparation method for high-capacity oligographene according to claim 7, characterized in that: In step S5, the centrifugal speed of the centrifuge is 8000±500r / min, and the centrifugal treatment time is 5-10min.
Citation Information
Patent Citations
Method for preparing porous graphene electrode material by air bubble template process and application of method
CN104934238A